Human resource management: the emerging trends - Agarwala, Tanuja (2002)
There is growing awareness of the importance and role of human resources in defining an organisation's cutting edge. Today's competitive business climate presents the HRM function with a number of important challenges and opportunities. Dramatic advances in technology, new forms of employment, and focus on cost-cutting necessitates concomitant modifications in recruiting, selection, training, appraisals, rewards and other human resource practices. Present exploratory study examines the major factors that have brought about the need for innovations in human resource (HR) practices. Further to understand the emerging trends and the nature of innovations in human resource practices, the study generated examples of innovative practices for each HR practice category. Since there is an increased pressure to measure HR effectiveness, present study also focussed on identifying key employee and organisational outcomes that were likely influenced by innovative HR practices. - Reproduced.
Keywords: Human resources development